Analisis Tren Dan Perbandingan Rasio Islamicity Performance Pada Bank Syariah Mandiri, BANK Muamalat Indonesia, Bank BRI Syariah Dan Bank BNI Syariah Periode 2011-2014 - Harvita Ayu Lutfiandari; Dina Fitrisia Septiarini (Universitas Airlangga, 2016)
This study is aimed to investigate the trend of financial performances and the difference of Islamicity Performance Ratioamong Islamic banks in Indonesia during 2011-2014. The quantitative approach of purposive sampling is used as the research method. The data collected frombank’s annual financial statements (2011-2014) used as sample: Bank Syariah Mandiri, Bank Muamalat Indonesia, Bank BNI Syariah and BRI Syariah. The data collected then analyzed using the trend analysis and ANOVA. Six variables: PSR, ZPR, EDR, DEWR, IIR and IsIR, are used as proxies for Islamicity Performance Ratio.Trend analysis shows that BRI Syariah has better PSR, ZPR, EDR, IsIR compared to other banks except for DEWR. IIR of Bank Muamalat is the best among others. Comparative analysis shows there are differences of Islamicity Performance Ratioamong Islamic banks in terms of PSR, EDR and DEWR, nevertheless there is no difference in terms of ZPR, IIR and IsIR.